Hepatic nNOS impaired hepatic insulin sensitivity through the activation of p38 MAPK. Issue 3 (March 2021) - Zhao, Tianxue; Li, Qian; Mao, Qianyun; Mu, Kaida; Wang, Chen
Abstract : Neuronal nitric oxide synthase (nNOS) interacts with its adaptor protein NOS1AP through its PZD domain in the neurons. Previously, we had reported that NOS1AP enhanced hepatic insulin sensitivity through its PZD-binding domain, which suggested that nNOS might mediate the effect of NOS1AP. This study aimed to examine the role and underlying mechanisms of nNOS in regulating hepatic insulin sensitivity. nNOS co-localized with NOS1AP in mouse liver. The overexpression of NOS1AP in mouse liver decreased the level of phosphorylated nNOS (p-nNOS (Ser1417)), the active form of nNOS. Conversely, the liver-specific deletion of NOS1AP increased the level of p-nNOS (Ser1417). The overexpression of nNOS in the liver of high-fat diet-induced obese mice exacerbated glucose intolerance, enhanced intrahepatic lipid accumulation, decreased glycogen storage, and blunted insulin-induced phosphorylation of IRbeta and Akt in the liver. Similarly, nNOS overexpression increased triglyceride production, decreased glucose utilization, and downregulated insulin-induced expression of p-IRbeta, p-Akt, and p-GSK3beta in the HepG2 cells. In contrast, treatment with Nω-propyl-L-arginine (L-NPA), a selective nNOS inhibitor, improved glucose tolerance and upregulated insulin-induced phosphorylation of IRbeta and Akt in the liver of ob/ob mice. Furthermore, overexpression of nNOS increased p38MAPK phosphorylation in the HepG2 cells. In contrast, inhibition of p38MAPK with SB203580 significantly reversed the nNOS-induced inhibition of insulin-signaling activity (all P < 0.05). This indicated that hepatic nNOS inhibited the insulin-signaling pathway through the activation of p38MAPK. These findings suggest that nNOS is involved in the development of hepatic insulin resistance and that nNOS might be a potential therapeutic target for diabetes.